Passive dynamic turning in 3D biped locomotion: an extension to passive dynamic walking. (1st February 2016) - Sabaapour, M.R.; Hairi Yazdi, M.R.; Beigzadeh, B.
Abstract: Passive dynamic walking usually refers to a kind of walking where a biped walker is able to walk downhill, without any actuation or control, just due to the gravity. Although most of works done in this regard have concentrated on passive walking along a straight line, in this paper we extend this concept to a more general case of locomotion, i.e. turning or walking along curved path. We call the novel extension passive turning, a nd categorize it to two types of finite and infinite. We showed that the finite type is still applicable on a typical downhill or ramp, while the infinite type is only practical on a specific surface profile that we call it helical ramp . Furthermore, several stability and parameter analysis are also conducted to evaluate more aspects of this notion. We highlighted that surprisingly, the passive straight walking is actually a special case of passive turning, just with infinite radius of turn and less asymptotical stability. It should be noted that the present study is performed using a model of an arc - foot three - dimensional (3D) compass gait walker. Abstract :